INFLUENCE OF A PULSED MAGNETIC FIELD ON THE ELECTRICAL PROPERTIES OF NANOPOWDER SYSTEM BASED ON ZIRCONIA - Artem Shylo; Aleksandr Doroshkevich; Tetyana Konstantinova; Igor Danilenko (Acta Metallurgica Slovaca, 2017)
A technique for studying of electrical characteristics based on electrochemical impedance spectroscopy of sealed nanopowder compact sets from a powder based on ZrO2 was proposed. The possibility of using this technique for studying of influence of pulsed magnetic field on a charge state of the surface of zirconia nanoparticles is shown. It is established that the action of a weak pulsed magnetic field leads to redistribution of free charge carriers between the volume and the surface of nanoparticles. In particular, different processing times lead to different impedance behaviour: treatment of a pulsed magnetic field with a pulse repetition frequency f = 1 Hz and an exposure time t <15 min leads to an irreversible decrease in the conductivity of the nanoparticle surface by two times (from 3.47 • 10-5 to 1.72 • 10-5 Ohm-1 • m-1), and processing with exposure time 15 <t <90 min leads to its increase by 10 times. Thus, the treatment of PMF causes formation in the near-surface zone of nanoparticles of a region depleted of charge carriers.